An Application of Discriminant Analysis in Classification of Financial Distress of Non-Life Insurance Companies - Phanmalee*, R.; Atthirawong, W. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The purpose of this research is to study factors affecting financial distress of Non-life Insurance Companies and classify their financial distress into solvent and insolvent insurers using discriminant analysis. The validity of the proposed model is measured by the accuracy rate of classifications. The model gives 88.30% correctly classified with 6.38% type I error and 14.44% type II error. Hence, it can be claimed that the model performs reasonable well in classifying financial distress. Keywords: Discriminant Analysis, Insolvent Insurer and Solvent Insurer, Financial Distress, Fisher’s Linear Discriminant Analysis, Stepwise Procedures. Corresponding author: E-mail: rat_kmitl@yahoo.com and walailak_ut@yahoo.com